2021
DOI: 10.1186/s13071-021-04596-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and expression analysis of annexin B3 and B38 as secretory proteins in Echinococcus granulosus

Abstract: Background Cystic echinococcosis is a parasitic zoonotic disease, which poses a threat to public health and animal husbandry, and causes significant economic losses. Annexins are a family of phospholipid-binding proteins with calcium ion-binding activity, which have many functions. Methods Two annexin protein family genes [Echinococcus granulosus annexin B3 (EgAnxB3) and EgAnxB38] were cloned and molecularly characterized using bioinformatic analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Among the most frequently identified protein families in the Anisakis secretome, attention should be paid to the annexin superfamily. Annexins have multiple functions, such as in cellular anti-inflammation, signal transmission, anticoagulation, ion channel regulation, membrane repair, and membrane transport, and likely participate in cell proliferation, differentiation, and apoptosis [41,42]. Furthermore, parasite annexins are considered potential drug and vaccine targets [43].…”
Section: Discussionmentioning
confidence: 99%
“…Among the most frequently identified protein families in the Anisakis secretome, attention should be paid to the annexin superfamily. Annexins have multiple functions, such as in cellular anti-inflammation, signal transmission, anticoagulation, ion channel regulation, membrane repair, and membrane transport, and likely participate in cell proliferation, differentiation, and apoptosis [41,42]. Furthermore, parasite annexins are considered potential drug and vaccine targets [43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that annexins of E . granulosus s.s. might play an important role in parasite-host interactions and demonstrated that the level of Eg ANXB3 transcription was increased from PSCs to adults [ 23 , 30 ]. This indicates that it has a potential role during the adult stages of infection in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted the crucial role of annexins in parasite growth, development, maintenance of cellular structural integrity, and the host's immune response against parasites [29,30,31,32]. For instance, Song et al [33] emphasized the potential signi cance of annexin B3 and annexin B38 in the invasion and development of Echinococcus granulosus protoscoleces. In our investigation, we observed the upregulation of annexin A1, annexin A7, annexin A5, and annexin A4 in the sparganum stages, while other annexins (annexin A3, annexin A2, annexin A13, and annexin A11) exhibited upregulation in the egg stage.…”
Section: Validation Of Depsmentioning
confidence: 99%